Effect of Stool Movement on A Physiotherapist MSD Risk During Manual Lymphatic Drainage: A Case Report - Jacquier-Bret, Julien; Gorce, Philippe (International journal of health sciences and research, 2022)
[Background] Physiotherapists have a high prevalence of musculoskeletal disorders (MSDs). The study of stool movements performed by the physiotherapist during manual lymphatic drainage has never been treated. It is known that the use of a stool allows improving the posture. [Purpose] The aim of the present work was to analyse the stool movements and its contribution in the prevention of work-related MSDs during the practice of manual lymphatic drainage through the analysis of postures over a period of 6 months. It can be hypothesized that the stool use should reduce MSD risk. [Participant(s) and Methods] Ten 20-minutes manual lymphatic drainage performed by a 39-years physiotherapist were recorded by two numerical cameras. Each stool movement (displacement/repositioning) and its duration were quantified. The posture adopted by the physiotherapist before and after each movement stool was defined by neck, trunk, and upper and lower limbs joint angles. The MSD risk associated with each posture was quantified using the Rapid Upper Limb Assessment (RULA). [Results] Eighty-six stool displacement/repositioning were identified. Joint ranges were characterized by a mean (± standard deviation) for the 10 massages performed. The difference in RULA score between the pre- and post- stool movement postures was computed to highlight the potential risk of MSDs. Results illustrated that 19% (16) of the stool movements (56% repositioning and 44% displacement) led to an increase in the RULA score. The posture adopted as a result of stool movements presented a greater risk of MSDs. Some recommendations have been proposed. [Conclusion] Manual lymphatic drainage activities over a long period of time expose physiotherapists to significant MSD risks even when using a rolling stool. Quick changes are needed to prevent their occurrence. During displacement or repositioning, it appears necessary to modify habits and behaviours to reduce the RULA score and therefore the MSD risk. This approach can be extended over a longer period of time including more subjects in order to quantify individual risks and propose recommendations. Key words: Musculoskeletal disorders, Physiotherapy, Posture, Ergonomics, RULA, Massage, Manual lymphatic drainage.